Sex and Exercise Intensity Do Not Influence Oxygen Uptake Kinetics in Submaximal Swimming - Reis, Joana F.; Millet, Gregoire P.; Bruno, Paula M.; Vleck, Veronica; Alves, Francisco B. (Frontiers in Physiology, 2017)
The aim of this study was to compare the oxygen uptake ( ) kinetics in front crawl between male and female swimmers at moderate and heavy intensity. We hypothesised that the time constant for the primary phase kinetics was faster in men than in women, for both intensities. Nineteen well trained swimmers (8 females mean ± SD; age 17.9 ± 3.5 yr.; mass 55.2 ± 3.6 kg; height 1.66 ± 0.05 m and 11 male 21.9 ± 2.8 yrs; 78.2 ± 11.1 kg; 1.81 ± 0.08 m) performed a discontinuous maximal incremental test and two 600-m square wave transitions for both moderate and heavy intensities to determine the kinetics parameters using mono- and bi-exponential models, respectively. All the tests involved breath-by-breath analysis of front crawl swimming using a swimming snorkel. The maximal oxygen uptake was higher in men than in women (4492±585 ml∙min-1 and 57.7±4.4 ml∙kg-1∙min-1 vs 2752.4±187.9 ml∙min-1 (p≤0.001) and 50.0±5.7 ml∙kg-1∙min-1(p= 0.007), respectively). Similarly, the absolute amplitude of the primary component was higher in men for both intensities (moderate: 1736±164 vs 1121±149 ml∙min-1; heavy: 2948±227 vs 1927±243 ml∙min-1, p≤0.001, for males and females, respectively). However, the time constant of the primary component (τp) was not influenced by sex (p=0.527) or swimming intensity (p=0.804) (moderate: 15.1 ± 5.6 vs 14.4 ± 5.1 s; heavy: 13.5 ± 3.3 vs 16.0 ± 4.5 s, for females and males, respectively). The slow component in the heavy domain was not significantly different between female and male swimmers (3.2 ± 2.4 vs 3.8 ± 1.0 ml∙kg-1∙min-1, p=0.476). Overall, only the absolute amplitude of the primary component was higher in men, while the other kinetics parameters were similar between female and male swimmers at both moderate and heavy intensities. The mechanisms underlying these similarities remain unclear.